Palladium Nanoparticles Stabilized by an Ionic Polymer and Its Application in Heck Reaction - Zhou, Bo; Juan Xu, Shi; Zhang Gou, Gao; Wu, Na; Liu, Wei (Asian Journal of Chemistry, 2015)
The palladium nanoparticles immobilized on the surface of poly(vinyl chloride)-supported pyridinium (PVC-Py-Pd0) were prepared by using the corresponding functionalized polymer and palladium chloride in ethanol solution. The palladium nanoparticles catalyst (PVC-Py-Pd0) was stable in the air and exhibited significant catalytic activity for Mizoroki-Heck coupling reaction of bromobenzene or iodobenzene with styrene under milder operating conditions. The catalytic system presented here showed several merits such as short reaction time, excellent yields of products, simple experimental and isolated procedure. Furthermore, the catalyst can be easily recycled and reused for at least five times with consistent activities.